2394. A Longitudinal Study of the Effect of Renal Failure on Readmission Rates of Patients with Clostridioides difficile - Destache, Christopher J (Open Forum Infect Dis, 2019)
BACKGROUND: Clostridioides difficile Infection (CDI) is a highly contagious bacterium that can be transferred from an infected surface. In this study, the Nationwide Readmissions Database was used to assess the risk of 30-, 60-, and 90-day readmissions in patients with comorbid CDI and renal failure (RF). METHODS: Using the Nationwide Inpatient Sample (NIS, 35 million hospitalizations/year) and the Nationwide Readmissions Database (NRD, 36 million/year), CDI in renal insufficient patients were identified. Years 2001–2014 of the NIS, as well as years 2010–2014 of the NRD were used for analysis. Chronic kidney disease (CKD) was based on the stage of the disease using IDC-9-CM coding (585.1–585.5). ICD-9-CM 585.6 was used for end-stage renal disease (ESRD). All analyses were done in R version 3.4.3. RESULTS: Over the 14 year period, the proportion of inpatients with CDI and RF increased from 0.004% (95% CI, 0.0038%-0.0042%) to 0.010% (95% CI, 0.0100%-0.0104%) in 2014. Inpatient RF and CDI increased a mean of 220,827 people over the 14 years. Inpatient CDI and RF prevalence is described as linearly increasing trend (Figure 1). Median age (2001–2014) for RF patients with CDI decreased 5 years to 68 (95% CI, 68–69). Using this model, expected CDI infections in RF to increase to 437,605.1 (95% CI, 427,984.2–447,380.8) hospital inpatients in 2018. In patients with CDI and CKD, ESRD is a significant predictor of 30-, 60-, and 90-day readmission. CONCLUSION: Using the NIS and NRD identified ESRD patients as a significant predictor of readmission for 30-, 60-, and 90-days. CDI infections in ESRD are expected to increase substantially by 2018. [Image: see text] DISCLOSURES: All authors: No reported disclosures.